IMPROVING STUDENTS' SPEAKING ABILITY BY USING INFORMATION GAP TECHNIQUE - Ilmasruroh Ilmasruroh; Regina Regina; Wardah Wardah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThe purpose of this study is to improve students’ speaking ability by using information gap technique to the eighth grade class F students of SMP Negeri 1 Rasau Jaya in academic year 2018/2019. This study was conducted by applying classroom action research method which is appropriate to overcome the existing problem faced by the students. The differences between spoken and written of English words caused the students difficult to pronounce English correctly. It makes them afraid to speak English in the classroom. The researcher used observation and measurement techniques to collect the data and used the observation checklist and field notes as the tools to collect the data in order to get the research finding. The researcher conducted this study in two cycles and the results showed that the use of information gap technique improved the students’ speaking ability in the aspect of the students’ pronunciation which became the problem in this study. It could be seen from the students’ mean score from the first cycle which was 65 to the second cycle which achieved 77. Through information gap the students got opportunities to practice their speaking in the classroom. Each student got chances to correct each other’s mistakes and shared information. In conclusion, the use of information gap technique can improve the students’ speaking ability.Keywords : Improving, Students’ Speaking Ability, Information Gap Technique